REGISTROS DE REPRESENTAÇÃO SEMIÓTICA E GEOMETRIA DINÂMICA PARA O ENSINO DE CONGRUÊNCIAS DE FIGURAS GEOMÉTRICAS PLANAS - Fogaça, Letícia dos Santos (2015)
In this survey, conducted in the Franciscan University in Santa Maria - RS, we had up to analyze how students of a higher education group, in the discipline of geometry I, the degree course in mathematics, build the concept of congruence of figures flat geometric, through semiotic representation registers and dynamic geometry. It emphasizes its qualitative character, in the form of a case study, in which data collection methods accounted for the analysis of the productions of the students. Four teaching units were developed that led to the construction of the concept of congruence of plane figures and classic cases of congruence of triangles using different registers of representation, such as registration figural, mental, computational, discursive and algebraic. Data analysis was made from the analysis of semiotic representation registers produced by the students. Overall, the students presented no difficulties in carrying out the treatments, because they could carry over into a single record. The difficulty resided in conversions between different records. Research results showed that the goal was achieved, as the proposed activities enabled the construction and understanding of the concept of congruence of plane figures by means of semiotic representation registers using the GeoGebra, which was detected by the fact that the students manage to perform treatments and conversions, at least two different records.